Reduction of Acanthamoeba Cyst Density Associated With Treatment Detected by In Vivo Confocal Microscopy in Acanthamoeba Keratitis. Issue 4 (April 2019) - Wang, Ye Elaine; Tepelus, Tudor Cosmin; Gui, Wei; Irvine, John A.; Lee, Olivia L.; Hsu, Hugo Y.
Abstract : Purpose: Acanthamoeba keratitis (AK) is a severe vision-threatening ocular infection that is frequently a diagnostic challenge. Treatment course is lengthy and often not fully effective. Contact lens wear has been recognized as the prime risk factor for AK. In vivo confocal microscopy (IVCM) is a noninvasive imaging modality that allows direct visualization of potential causative pathogens in real time with an established utility in the diagnosis of AK. In this study, we aim to assess the utility of IVCM in monitoring disease progression in contact lens wearers with culture-confirmed keratitis. Methods: Fourteen eyes from 11 patients with culture-confirmed AK were included in this retrospective study. IVCM was performed during the patient's initial visit and all follow-up visits. All available confocal sequences were reviewed and graded in a masked fashion. Density of Acanthamoeba cyst infiltration and changes in the cyst density as a percentage of baseline cyst density measured at each patient's initial visit were calculated. A univariate regression analysis was performed to assess the association between treatment and changes in cyst density per month of treatment. Results: Acanthamoeba cysts were identified by IVCM in all of these culture-confirmed cases of keratitis. Mean cyst density in the central cornea at presentation was 99 ± 64.9 cells per square millimeter (range, 38–255/mm 2 ). Cyst density in our study population significantly decreased by approximately 5.3% with each month of antiamebic treatment ( P = 0.001; R 2 = 0.41). Conclusions: Reduction in Acanthamoeba cyst density with treatment can be monitored by IVCM, which in turn can be used clinically in prognostication and disease monitoring of AK.